YIELD AND CURCUMIN CONTENT STABILITY OF FIVE UB CLONES OF TEMULAWAK (Curcuma xanthorriza Rox.) - Wardiyati, Tatik; Kuswanto, Kuswanto; Azizah, Nur (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Interactions between genotype and environment is affect yield and curcumine content of temulawak (Curcuma xanthorrhiza Rox). The aims of the study was to determine stability of yield and curcumine content in diffrent enviromental condition. Field experiment was conducted during 12 month of year 2010, and Randomized block design with three replications was applied at four locations : Sragen, Malang, Pasuruan and Sumenep. The materials tested consists of five clones : UB1, UB2, UB3, UB4, UB5 included control ( Balitro clone). The results showed that the stability of the rhizome yield in each locations , achieved by UB3 and UB4 clones. The highest rhizome weight was obtained by UB2 at 34,63 t/ha, while the constant high curcumin content was obtained by UB4. Clones UB1 and UB5 suitable to be developed on marginal lands and clone UB2 adaptive on high fertility environment. Key words :temulawak, adaptation, clones